Introduction of a national minimum wage reduced depressive symptoms in low-wage workers: a quasi-natural experiment in the UK - Reeves, A; McKee, M; Mackenbach, J; Whitehead, M; Stuckler, D (John Wiley & Sons Ltd, 2016)
Does increasing incomes improve health? In 1999, the UK government implemented minimum wage legislation, increasing hourly wages to at least £3.60. This policy experiment created intervention and control groups that can be used to assess the effects of increasing wages on health. Longitudinal data were taken from the British Household Panel Survey. We compared the health effects of higher wages on recipients of the minimum wage with otherwise similar persons who were likely unaffected because (1) their wages were between 100 and 110% of the eligibility threshold or (2) their firms did not increase wages to meet the threshold. We assessed the probability of mental ill health using the 12-item General Health Questionnaire. We also assessed changes in smoking, blood pressure, as well as hearing ability (control condition). The intervention group, whose wages rose above the minimum wage, experienced lower probability of mental ill health compared with both control group 1 and control group 2. This improvement represents 0.37 of a standard deviation, comparable with the effect of antidepressants (0.39 of a standard deviation) on depressive symptoms. The intervention group experienced no change in blood pressure, hearing ability, or smoking. Increasing wages significantly improves mental health by reducing financial strain in low-wage workers. © 2016 The Authors. Health Economics published by John Wiley and Sons Ltd.